KINERJA PEGAWAI PADA BAGIAN HUMAS SEKRETARIAT DAERAH KABUPATEN KUTAI BARAT - Paollo Diego Y.G.Tambingon (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The results of this study have indicated good performance of the apparatus but still not optimal. Supporting factors contributing to Organizational Performanceare the Government Regulations (PP No. 29 of 2004, Regulation No.101 of 2001, Public policy No. 42 of 2008. Where a the factors that hinder the achievement of the performance are the limited allocation of rooms for work of public relations and protocol in the West Kutai Regional Secretariat that are less than a dequate and flexibility in performing work activities.